Perceptions and practices of imaging personnel and physicians regarding the use of brain MRI for dementia diagnosis in Uganda - Rita Nassanga; Noeline Nakasujja; Mark Kaddumukasa; Stephen E. Jones; Martha Sajatovic; Michael Grace Kawooya (PLoS ONE, 2025)
Introduction Diagnosing dementia remains challenging in low-income settings due to limited diagnostic options and the absence of definitive biomarkers. The use of brain MRI in the diagnosis of dementia is infrequent in Uganda, and even when it is used, subtle findings like mild regional atrophy are often overlooked, despite being crucial for imaging diagnosis. Objective The purpose of this study was to explore the perceptions and practices of imaging personnel and physicians regarding the use of brain MRI as a diagnostic approach for dementia in Uganda. Methods This was an exploratory qualitative study involving radiologists, technologists, senior house officers and psychiatrists. The participants were 25 in total. Data was collected through key informant interviews and focus group discussions and analyzed thematically using an inductive approach. Results The study revealed three key themes: Brain MRI Practices for Diagnosing Dementia, Facilitators of Appropriate MRI Use, and Barriers to Appropriate Use of Brain MRI. Sub-themes under these themes included cost considerations, poor and good MRI practices, MRI as a standard operating procedure, positive attitudes towards brain MRI, and barriers such as structural, financial, operational, technical, and patient-related issues. Participants acknowledged the high accuracy and superiority of brain MRI for diagnosing dementia and recognized it as the standard of care. However, its use in Uganda is limited due to high costs, restricted access, mechanical failures, patient claustrophobia, myths and misconceptions, and interpretation difficulties by radiologists and inappropriate protocols by technologists. Conclusion The study identifies barriers to effective brain MRI use for dementia diagnosis in Uganda, including limited training, high costs, and uneven equipment distribution. Despite this, providers are positive about MRI adoption. Enhancing training, awareness, and phased rollouts can improve outcomes. Future research should focus on similar low-resource settings for validation.